The Keysha diaries. Volume one - Sewell, Earl. (Don Mills, Ont. : Harlequin Kimani Tru, 2013)
Presents two novels by Earl Sewell: in "Keysha's Drama" African-American sixteen-year-old Keysha Kendall takes up with a bad crowd as she struggles to adjust to life in her affluent biological father's home after her mother is arrested; and in "If I Were Your Boyfriend" after having her reputation ruined by a girl who planted drugs on her, Keysha returns to school to find she is a social outcast and builds a relationship with Wesley Morris, a sexy guy who wants to help her, even though her family does not approve of him.
Keysha's drama -- If I were your boyfriend.
Young Adult
Young Adult
Keywords: African American teenagers -- Fiction; Children of single parents -- Fiction; Parent and child -- Fiction; Stepparents -- Fiction; Juvenile delinquents -- Fiction; Drug traffic -- Fiction; High schools -- Fiction; African American teenagers -- Fiction; Children of single parents -- Fiction; Parent-child relationship -- Fiction; Stepparents -- Fiction; Juvenile delinquency -- Fiction; Drug traffic -- Fiction; High schools -- Fiction